(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The present study aimed to evaluate the production of melon seedlings in protected environment due to the use of substrates based on crushed manioc branches submitted to different composting periods. The experiment was conducted in a completely randomized design, in a 5 x 2 factorial scheme, whose treatments corresponded to a combination of five composting periods of crushed cassava branches (0, 30, 60, 90 and 120 days) and two varieties of melon (Gaúcho Casca de Carvalho and Melão Amarelo) in a protected environment. In the emergence of the seedlings, the evaluations of the index of emergency speed and emergency percentage were started. Plant height, root diameter, root system length, dry shoot mass, root dry mass, total dry mass and Dickson quality index were evaluated at 30 days after sowing. The data were submitted to analysis of variance. The effects of composting time were evaluated by polynomial regression and the effects of the varieties by the F test (5%), verifying and unfolding the interactions. The varieties presented satisfactory physiological parameters in relation to the composting periods of the substrate, where the Yellow Melon presented better development results. The Melon Yellow variety presents better development of the seedlings in relation to the variety Gaúcho Casca de Carvalho in the conditions of the present study. The composting period of 120 days is the most suitable for the production of melon seedlings, since they present better shoot development, root system and increases in total dry mass.